Size Dependence of the Magnetoelastic Properties of Metallic Glasses for Actuation Applications - Ariane Sagasti; Jon Gutiérrez; Andoni Lasheras; José Manuel Barandiarán (Sensors, 2019)
We present an exhaustive study of the magnetoelastic properties of 24 strips with different rectangular dimensions, cut from a long ribbon of Metglas® 2826MB3. The strips have a length-to-width ratio R = L/w ranging from 2 to over 20. Significant variations of the apparent saturation Young’s modulus and the ΔE effect with strip geometry, changing from 160 GPa and 4% for L = 10 mm, w = 5 mm and R = 2, to 164 GPa and 9.6% for L = 35 mm, w = 1.7 mm and R = 20.6, have been observed. In order to obtain the highest values of the ΔE effect, the magnetomechanical coupling coefficient, k, and the quality factor of the resonance, Q, a value R > 14 is needed. The effective anisotropy field Hk*, taken as the minimum of the E(H) curve, and its width ΔH, are not as strongly influenced by the R value, and a value of R > 7 is enough to reach the lowest value. From our measurements we infer that the formerly predicted value of R > 5 needed for a good magnetic and magnetoelastic response of the material must be actually regarded as the lowest limit for this parameter. In fact, we show that the demagnetizing factor N, rather than the length-to-width ratio R, is the parameter that governs the magnetoelastic performance of these strips.